Modern approaches to the qualifications assessment - Vladimir I. Blinov; Olga F. Batrova; Ekaterina Yu. Esenina; Alla A. Faktorovich (Moscow Polytechnic University, 2022)
The article is devoted to the modern methodology for the qualifications assessment procedures. Based on an analysis of international experience and modern Russian legislation the principles of qualifications assessment and the assessment tools developing algorithm are described.